Círculos y cuadraturas: presiones inflacionarias y enfermedad holandesa en la Venezuela bolivariana - Calderón-Vázquez, Francisco José (Eumed.net, 2010)
The analysis of inflationary pressures in Bolivarian Venezuela, in their origins and causes (historical and contemporary ones) has to be put into relation to the economic and monetary policy options adopted by the current Venezuelan government, in the framework of the challenges and choices a developing Economy has to face. For getting out of that complicated and involved cycle of underdevelopment. Inflationary pressures deconstruction is achieved by mean of interactions between the main aggregates and the behavior of such variables as public expenditure, prices and consumption. They are placed into relation to the socio-economic and historical background of Venezuelan development. Particularly, the "Dutch disease" theoretical and practical co-ordinates are used here.
Circles and squaring: inflationary pressure and dutch disease in bolivarian Venezuela
Keywords: Inflación; Venezuela; Política monetaria; Inflationary pressures; overliquidity; tax policies; monetary policies; Dutch disease